Morphology of the vertebral artery in Asian population - Alfaouri-Kornieieva, Maryna; Al-Hadidi, Azmy M (Asian Journal of Medical Sciences, 2014)
Background: Recent clinical trials have shown a rising trend of stroke in Asian population. Approximately 20% strokes of total occur at the vertebrobasilar basin that supplies the occipital lobes of the brain, the cerebellum, and the brainstem. The anatomical features and variability of the third segment of the vertebral artery (VA) in Asians are analyzed in this study. Methods: A prospective cohort study of 68 consecutive Asian patients underwent MRA examination for head and neck in the Department of Radiology of Hospital of University of Jordan from 1.10.2011 to 30.04.2012. The 116 VA were analyzed on the obtained angiograms. Results: The third segment (V3) of the VA was studied according to its conventional division into vertical, horizontal, and oblique parts. The mean outer diameter of the V3 varied up 3.18 ± 0.73 to 4.28 ± 1.08 mm. The parameter prevailed on the left in 91% cases and was greater in males, than in females. The distal loop of the VA projected downward in 26 cases on the right (78%) and in 28 cases on the left (74%). The tortuosity of loop?formations of V3 was evaluated subject to angles between their ascending and descending bends. Conclusion: In comparison with other ethnic groups, the V3 of the VA in Asians has lesser outer diameter, especially along its oblique part; the zero?distance between the occipital bone and horizontal segment of VA occurs more often (up to 26%); the Lang’s III type of V3 variability is the most common in Asians. DOI: http://dx.doi.org/10.3126/ajms.v5i4.6150 Asian Journal of Medical Sciences 2014 Vol.5(4); 84-88